Anthropometry, strength and benchmarks for development: A basis for junior rowers' selection? - Lawton, T. W.; Cronin, J. B.; Mcguigan, M. R. (Journal of Sports Sciences, 2012)
The aims of this study were to establish whether anthropometry, muscle strength and endurance accounted for differences between junior and senior elite rowing ergometer performance, and to determine annual development rates for juniors associated with training. Twenty-six junior (8 females, age 18.0±0.3 years and 18 males, age 17.9±0.2 years) and 30 senior (12 females, 23.7±3.0 years and 18 males, 24.0±3.9 years) heavyweight rowers, were assessed anthropometrically, performed a 2000-m ergometer time-trial, and completed various muscular strength and endurance tests. There were no anthropometrical differences between males; however after controlling for body-fat and standing-height, senior females were of greater body-mass (70.5±4.6 kg and 77.2±5.9 kg, P = 0.01) and sitting-height (89.8±2.2 cm and 92.2±6.1 cm, P = 0.04) than juniors. Moderate to very large standardised differences in all strength and endurance tests were observed between juniors and seniors (effect size (ES) range 0.9-1.9). Greater development rates (5.0% to 6.0%) and adjusted 2000-m performance was associated with upper-body strength (males) and endurance (females). In conclusion, after identification of desirable anthropometry, the 2000-m ergometer potential of juniors may be accounted for by upper-body strength and endurance